2017
DOI: 10.1242/jcs.201400
|View full text |Cite
|
Sign up to set email alerts
|

Sub-mitochondrial localization of the genetic-tagged mitochondrial intermembrane space-bridging components Mic19, Mic60 and Sam50

Abstract: Each mitochondrial compartment contains varying protein compositions that underlie a diversity of localized functions. Insights into the localization of mitochondrial intermembrane space-bridging (MIB) components will have an impact on our understanding of mitochondrial architecture, dynamics and function. By using the novel visualizable genetic tags miniSOG and APEX2 in cultured mouse cardiac and human astrocyte cell lines and performing electron tomography, we have mapped at nanoscale resolution three key MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 91 publications
2
33
0
Order By: Relevance
“…Subunit MIC10 plays a central role in the yeast MICOS system (31), and MIC10 oligomerization induces MOM bending at CJs (17). Electron tomography analysis revealed that MIC19 and MIC60 were enriched inside cristae and localized at CJs (346). Moreover, the latter study provided evidence that MIC19 interacted with subunit IV of CIV.…”
Section: Fig 7 Key Mechanisms That Govern Dynamic Changes In Mitochmentioning
confidence: 77%
“…Subunit MIC10 plays a central role in the yeast MICOS system (31), and MIC10 oligomerization induces MOM bending at CJs (17). Electron tomography analysis revealed that MIC19 and MIC60 were enriched inside cristae and localized at CJs (346). Moreover, the latter study provided evidence that MIC19 interacted with subunit IV of CIV.…”
Section: Fig 7 Key Mechanisms That Govern Dynamic Changes In Mitochmentioning
confidence: 77%
“…Another intriguing possibility is that the synthesis of PE by Psd1p in the IM is somehow directly coupled to the incorporation of this lipid into partially or fully assembled complex III. Recently, a subunit of complex IV was found to associate with the MICOS subunit, Mic19, in mammalian cells by EM tomography and immunoprecipitation (44). As the MICOS complex was suggested to work in concert with Ups2p to regulate mitochondrial PS/PE metabolism in yeast (26), potentially, contact sites between the OM and IM could facilitate the transport of ER-derived PE to complex IV more directly than it can to complex III.…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian cells, MICOS and SAM form a stable supercomplex that was termed mitochondrial intermembrane space bridging complex (MIB) (Fig. ) . These interactions support the import of a subset of mitochondrial proteins, and, importantly, they establish contact sites between the two mitochondrial membranes .…”
Section: The Mitochondrial Contact Site and Cristae Organizing Systemmentioning
confidence: 99%